2007
DOI: 10.1136/jnnp.2006.087791
|View full text |Cite
|
Sign up to set email alerts
|

Influence of subjective visual vertical misperception on balance recovery after stroke

Abstract: Background: Subjective visual vertical (SVV) perception can be perturbed after stroke, but its effect on balance recovery is not yet known. Aim: To evaluate the influence of SVV perturbations on balance recovery after stroke. Methods: 28 patients (14 with a right hemisphere lesion (RHL) and 14 with a left hemisphere lesion (LHL)) were included, 5 were lost to follow-up. SVV perception was initially tested within 3 months after stroke, then at 6 months, using a luminous line, which the patients adjusted to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
87
0
14

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 31 publications
(27 reference statements)
5
87
0
14
Order By: Relevance
“…21 This notion is supported by previous research indicating that compared to lesions within the left MCA territory, those within the right MCA territory-and particularly to regions such as the insula and temporoparietal junction-often result in more severe distortion of spatial postural representation, as well as the visual and nonvisual subjective perception of the body's verticality. [22][23][24] Previous work by our group has also suggested that right hemisphere infarcts are more disruptive to the ability to regulate postural sway when standing, but only in the frontal plane. 14,[23][24][25] Future research is therefore warranted to study the effects of MCA infarct on the relationship between residual impairments in the subjective perception of one's posture and gait symmetry in this vulnerable population.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…21 This notion is supported by previous research indicating that compared to lesions within the left MCA territory, those within the right MCA territory-and particularly to regions such as the insula and temporoparietal junction-often result in more severe distortion of spatial postural representation, as well as the visual and nonvisual subjective perception of the body's verticality. [22][23][24] Previous work by our group has also suggested that right hemisphere infarcts are more disruptive to the ability to regulate postural sway when standing, but only in the frontal plane. 14,[23][24][25] Future research is therefore warranted to study the effects of MCA infarct on the relationship between residual impairments in the subjective perception of one's posture and gait symmetry in this vulnerable population.…”
mentioning
confidence: 96%
“…[22][23][24] Previous work by our group has also suggested that right hemisphere infarcts are more disruptive to the ability to regulate postural sway when standing, but only in the frontal plane. 14,[23][24][25] Future research is therefore warranted to study the effects of MCA infarct on the relationship between residual impairments in the subjective perception of one's posture and gait symmetry in this vulnerable population.…”
mentioning
confidence: 96%
“…The SVV is the measure investigated most often. It is frequently used in the diagnosis of vestibular disorders, but is poorly correlated with postural impairment (Bonan et al, 2007;Karnath, Ferber, & Dichgans, 2000;Pérennou et al, 2008). The SPV is altered in subjects with deficits of upright body orientation, both in the frontal and sagittal planes-for example, in subjects with pusher behavior or retropulsion after hemispheric lesions (Karnath et al, 2000;Manckoundia, Mourey, Pfitzenmeyer, Van Hoecke, & Pérennou, 2007;Pérennou et al, 2008).…”
mentioning
confidence: 99%
“…We also found that misperception of verticality in MS patients is correlated to the risk for falling evaluated by DGI scale. Prior studies suggested that the incapacity to detect visual verticality could be related to poor balance recover 27,28 . Despite of these studies have evaluated patients that suffered stroke, the findings highlight that some cortical areas are related to perception of verticality, and these sense is not just related to peripheral lesions.…”
Section: Discussionmentioning
confidence: 99%